Twisted roots : Latin America's living past - Montaner, Carlos Alberto (Algora Pub., 2003)
Examining the historical and cultural influences that have shaped Latin America, this syndicated international journalist and author suggests that they have made it into the most impoverished, unstable and backward region in the Western world."An indispensable book."--Mario Vargas Llosa